THE EFFORTS TO INCREASE ACTIVITY AND OUTCOMES OF LEARNING ABOUT MATHEMATICS CLASS XI THROUGH COOPERATIVE LEARNING MODEL TYPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) - Ari Kurniasih; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
So far, some think that mathematics is no more than counting and playing with formulas and statistics. The student simply accepts mathematics teaching in school without questioning why, and for what mathematics, and for what match should be taught. This research aims to improve the activities and results in study mathematics by cooperative learning design type student team achievement division (STAD). The kinds of this research are classroom action research (CAR), the research setting is XI IPS I State Senior High School 4 Yogyakarta (SMA Negeri 4 Yogyakarta) Academic year 2016/2017 consisting of 27 students. The data collecting technique is observation and test learning outcomes. The data analysis technique is descriptive qualitative research. This research indicates that by using the cooperative learning design type student team achievement division (STAD), there are improvements in activities and mathematics learning outcomes students in two cycles. This matter seen from the percentage average of observation results of learning activities students in I cycle; it is about 56,51% by enough criteria, and in cycle II are increased become 82,36%. Improvement learning outcomes are seen in cycle I from 27 students who fill up MCC amounted to 15 students in cycle II increased to 23 students who fill up Minimum Completeness Criteria (MCC).